The effect of dietary colostrum powder on performance, carcass yields and serum lipid peroxidation levels in Japanese quails (Coturnix coturnix japonica) - Akdemir, Fatih; Bayril, Tahir; Baran, Murat Sedat; Yildiz, Ahmet Sener; Kahraman, Mucahit; Orhan, Cemal; Şahin, Kazım (Taylor & Francis Ltd, 2018)
Colostrum is a nutrient-dense fluid secreted by female mammals for the first few days following birth. Colostrum can be supplemented to poultry diets as a feed additive due to its nutritious and performance-enhancing properties. This study was conducted to determine the effect of dietary colostrum powder (CL-P, Alpha Lipid Lifeline Colostrum, New Zealand) on growing performance, carcass weight and yield, organ weights, serum vitamins and malondialdehyde (MDA) levels in quails (Coturnix coturnix japonica). A total of 90 birds, one day old, were divided into 3 groups consisting of 6 replicate cages, 5 birds per cage. Birds were randomly fed on one of three diets: basal diet and basal diet supplemented with 2.5% or 5% of CL-P. At the end of the period of 42 days, CL-P supplementation increased final body weight (P < .0001), weight gain (P < .0001), feed intake (P = .03), feed efficiency (P < .0001), carcass weight (P < .0001) and carcass yield (P < .01). Amounts of serum MDA (P < .001) levels also increased with increasing supplemental CL-P. As a result, growth performance can be improved and serum lipid peroxidation can effectively be attenuated by dietary CL-P supplementation at 5% of diets in Japanese quail.
Keywords: Colostrum powder; Japanese quail; performance; lipid peroxidation